(3hbGjI GdQhGjI aj eSGFd GdgOGjIs - (3GdeMHhHj, GdMfaj, , HQgGf GdTQjYI, eMehO Hf YHjO Gddg Hf EHQGgje, (B673 (3gs
(3ChdgG (B:s
(3HYO GdHSedI ; MeO ef LYd GdYde CLd GdehGgH GdgfjI hCSfGgG hCYdi GdeQGJH GdSfjI hCSeGgGs
(3BNQgG (B:s
(3hbGdhG dh aj eYJbd GddSGf Ef GeJO Pdc hYde ETGQJg acPdc hEdG adG haj Zfe ePHhMI ajgG ejJIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3 / 818s
(3cTa GdXfhf (B2 / 2020s
(3gOjI GdYGQajf (B2 / 406s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3Gdabg GdMfHdjs